2019
DOI: 10.1016/j.lwt.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multifunctional yogurt-like product from germinated brown rice

Abstract: The suitability of germinated brown rice (GBR) for developing novel multifunctional yogurt-like products was evaluated. Crude brown rice, soaked brown rice and GBR for 48 h and 96 h were fermented (F-CBR, F-SBR, F-GBR48 and F-GBR96, respectively). The viability of the starter culture, acidification pattern, techno-functional properties, content of bioactive compounds [phenolic compounds, gamma-aminobutyric acid (GABA) and gamma-oryzanol], biological activity [antioxidant and angiotensin Iconverting enzyme (ACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 40 publications
2
26
3
2
Order By: Relevance
“…were used at different percentages in water, usually from 15% to 35%. This amount was selected to achieve optimal PBYL texture after gelatinization at high temperature [ 14 , 23 , 27 , 32 , 33 , 34 ]. Similar ratios were also used for cereal-legume blends including, for example, rice, soy, oat, barley and emmer flours [ 13 ], or rice, lentil, and chickpea flours [ 14 ].…”
Section: Texture: Role Of the Bioprocessing Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…were used at different percentages in water, usually from 15% to 35%. This amount was selected to achieve optimal PBYL texture after gelatinization at high temperature [ 14 , 23 , 27 , 32 , 33 , 34 ]. Similar ratios were also used for cereal-legume blends including, for example, rice, soy, oat, barley and emmer flours [ 13 ], or rice, lentil, and chickpea flours [ 14 ].…”
Section: Texture: Role Of the Bioprocessing Optionsmentioning
confidence: 99%
“…The use of cereal ingredients, for example, corresponds to PBYL characterized by carbohydrates content which is usually higher than dairy counterparts. Nevertheless, high concentration of fibers can be obtained by using whole grains, as in the case of YL products obtained with oat flakes and brown rice [ 27 , 34 ]. Besides dietary fibers, the use of pseudocereals and legumes also allows to obtain high level of high biological-value proteins, as reported when quinoa, soy, lupin, lentil and chickpea flours were used as the main YL ingredients [ 11 , 14 , 33 , 41 ].…”
Section: Nutritional and Functional Aspects: Matrix- And Fermentatmentioning
confidence: 99%
“…Recently, yoghurt‐like products were developed from BR, soaked BR, or GBR of 48 hr and 96 hr germination by lactic acid fermentation. Fermented GBR of 96 hr germination showed the highest phenolic concentrations, antioxidant activity, angiotensin converting enzyme inhibition, and panelists’ acceptability (Cáceres, Peñas, Martínez‐Villaluenga, García‐Mora, & Frías, ). Therefore, different highly acceptable and healthy food types can be produced from BR by optimization of processing conditions.…”
Section: Development Of Food Productsmentioning
confidence: 99%
“…It has been largely demonstrated that lactic acid fermentation improves sensory characteristics, nutritional quality, texture and safety of starch-containing vegetables including cereals [ 7 ]. Strong scientific evidence support the beneficial effects of lactic acid bacteria fermentation in cereal matrices by enhancing the content and bioavailability of phenolic compounds, γ-aminobutyric acid (GABA) and antioxidant, anti-hypertensive and anti-inflammatory activities [ 8 , 9 , 10 ]. A number of recent investigations have evidenced that cereals are good fermentable substrates for lactic acid bacteria (LAB) that can be used as raw materials for development of probiotic beverages with enhanced nutritional properties [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%